WORDS OF WONDERS : EKSPLORASI PENGALAMAN SISWA SEKOLAH DASAR DALAM MEMPERBANYAK KOSAKATA BAHASA BAKU - Sutomo; Evi Chamalah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
A strong command of vocabulary is pivotal in early language development, especially for young learners navigating cognitive and language skill growth. This research examines how fifth graders at SD Islam Sultan Agung 4 expanded their formal language lexicon using the Words of Wonders (WoW) digital tool. A case study methodology was adopted, with data gathered through classroom observations and semi-structured interviews. Analysis indicated that the WoW app significantly boosted learners’ motivation, prompting active participation and greater self-assurance in experimenting with newly acquired terms. Despite this progress, students struggled to consistently use these words in informal contexts. The application’s gamified design created a dynamic and engaging educational setting, amplified by teacher guidance and parental involvement. Recurring issues, such as vocabulary retention gaps and sporadic learner drive, highlight areas needing strategic support. Ultimately, this study underscores WoW’s efficacy as a vocabulary-enhancement platform while advocating for curriculum innovations that leverage interactive technologies to address evolving pedagogical demands.